Neutrophil extracellular traps (Nets) impact upon autoimmune disorders - Pruchniak, Michał Przemysław (Cent Eur J Immunol, 2015)
Friend or foe? This is often asked question when it comes to neutrophil extracellular traps studies. There is no simple answer to that. At the time of their discovery they were considered to be protectors of our well-being. Excellent pathogen fighting skills were described as purely beneficial. But it was not long before those guardians of immunity reveal their dark side. What seemed to be profitable could also take its toll. They are perfectly constructed, made from nucleic deoxyribonucleic acid ornamented with cytoplasmic and granular proteins, to fight invaders. But this unique build is prone to become considered by our body as a threat. Since there is a thin line which when crossed turns a savior into enemy, it was postulated that Nets can play a significant role in autoimmune disorders pathogenesis and disease exacerbation. Recent years have brought a new insight into autoimmune disorders trying to connect the old knowledge and suspicions with modern discoveries.